Influence of Manure, Nitrogen, Phosphorus and Potassium Fertilizer Application on Growth of One-year-old Oil Palms on Marginal Soil in Jonggol, Bogor, Indonesia - Sudrajat, Sudradjat; Sukmawan, Yan; Sugiyanta, Sugiyanta (Journal of Tropical Crop Science, 2014)
The oil palms (Elaeis guineensis Jacq.) are highlyefcient oil producers. It produces ve to seven timesmore vegetable oil per hectare than soybean, sunower,and rapeseed. The objectives of this research were tostudy the role of organic and N, P, and K fertilizers ongrowth of one-year-old immature oil palm on marginalsoil in Jonggol. The research was conducted at IPBCargill Teaching Farm (ICTF) of Oil Palm, Jonggol,Bogor,West Java from March 2013 to March 2014. Theexperiment was arranged in a factorial experimentfollowing a randomized block design with threereplications. The rst factor was organic fertilizer(manure) consisting of 0 (O), 15 (O1) and 30 (O2) kg pertree per year. The second factor was inorganic fertilizerconsisting of 0 (S0); 0.25 kg N + 0.25 kg P O + 0.39 kg 2 5K O(S ) 0.50 k N+ 0.50 kg P O + 0.78 kg K O(S ) 2 25 2 1and g 2per tree. The results demonstrated that application ofmanure up to 30 kg per tree per year did not affect thegrowth of one-year-old oil palm. Application of 0.50 kg N+ 0.50 kg P O + 0.78 kg K O highest 2 5 2 per tree gave theresult in increasing frond production, stem girth, and leafnutrient concentration. The results of leaf analysis andplant growth responses suggested that the rates ofmanure and inorganic fertilizers applied in this study arenot sufcient to improve young oil palm growth inmarginal soil in Jonggol.Keywords: cow manure, critical nutrient level, inorganicfertilizer, soil fertility, vegetative growth